Measurement of the paleodose in luminescence dating using the TM-OSL of quartz. (1st January 2021) - Chruścińska, Alicja; Palczewski, Piotr; Rerek, Tomasz; Biernacka, Magdalena; Lefrais, Yannick
Highlights: The OSL dating of sediments using quartz significantly improved. TM-OSL with 620 nm successfully used in the dating protocol instead of the CW-OSL. The age estimation based only on the fast OSL component in quartz. Avoiding the optical bleaching at higher temperature. Assessing the quality of OSL signal of grains at the stage of natural OSL measurement. Abstract: The optically stimulated luminescence (OSL) of quartz is widely used in luminescence dating and retrospective dosimetry. The signal exploited up to now in measurement protocol is complex. It is hard to check by standard measurements whether the fast component which is the most appropriate for the age estimation dominates in the total OSL signal. Recently, a new method called thermally modulated OSL (TM-OSL) was developed which allows the selective detection of the OSL components. The new measurement protocol called SAR TM-OSL uses only the fast OSL component to estimate the age. The shape of TM-OSL curve makes possible to distinguish aliquots whose OSL signal is not dominated by the fast OSL component at the first stage of the dating protocol. The new protocol is 30% more time consuming, but it can be easily optimized by stimulation with more powerful LEDs than those used in current experiments.